Dimensão fractal e ilhas de calor urbanas : uma abordagem sistêmica sobre as implicações entre a fragmentação das áreas verdes e o ambiente térmico do espaço urbano - Barros, Marcelo Paes de (2012)
Rapid urbanization, as a result of urban population growth, has been recognized as a critical process in urban areas. This rapid growth has led to demands for occupation of green areas, spaces for important cooling effect of urban environments. The reduction and fragmentation of urban green areas has directly influenced the quality of life in tropical cities. The present study aimed to evaluate the extension of the influence of green areas and its fragmentation, quantified by the fractal dimension, on the thermal environment of a place. The study was conducted in five districts of the southeastern of Cuiaba city, Mato Grosso, Brazil, heterogeneous spaces with large social contradictions, where urbanization was more intense in the period 1980 to 2010. The data collection methodology, established for the research, included measurements of air temperature, mobile and fixed, remote sensing and geographic information systems to determine the percentage of vegetated areas and the corresponding values of fractal dimension and other indices of landscape, addition to methods of curve fitting and of geostatistical treatment of data for analysis of the interrelationship between air temperature and the spatial patterns of urban forest fragments. In parallel, complementarily, questionnaires were applied to residents of the study area in order to determine which attributes of a place could explain the image of residence of the residents of this area. The analysis results confirmed the influence of fragments of arboreal vegetation on the air temperature of the environments analyzed, providing also the radius of this influence that ranged from 200 m to 500 m depending on time of day and season, dry or rainy. It was found that the fragmentation of the green areas, aptly described by the fractal dimension, has been more decisive in thermal environments with low percentages of vegetated area, and in such cases a less fragmented vegetation resulted in lower air temperatures. These results can provide subsidies for the development and implementation of urban projects aimed at improving environmental comfort for the entire population of the cities.